FENOMENA KEKKON IJU JOSEI DALAM MASYARAKAT JEPANG - Ayu Gardenia Lantang (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2018)
This paper is focus on the phenomenon of Kekkon Iju Josei in rural areas that represented by Tohoku prefecture and Niigata prefecture, Japan. This research is a qualitative research that describe the result of research was applied by analysis descriptive research. This paper aim to give an understanding of the background the increase of kekkon iju josei in rural societies in Japan. The results of analysis indicate several things, the first that the phenomenon of kekkon josei iju is arrange married and conducted for the purpose to increase number of people in rural areas in Japan. Second, that kekkon iju josei is motivated by the initiative and cooperation of local governments in the prefecture with the local authorities in the destination country, and matchmaking to facilitate and bring foreign women to married with men in rural areas in Tohoku and Niigata prefecture. Thirdly, that the majority of these immigrant women from the Philippines, China, Thailand and Korea. This is affected because there was an impression, interests and image Japan as a developing and rich countries from foreign womens which encourage them to come get married, work and settled in Japan. This is done so that they could have a better life than in their home country.